Risk Score for Prediction of Severe Postoperative Complications After Pancreaticoduodenectomy - Shah, Surendra; Bhandari, Ramesh S; Vaidya, Pradeep; Singh, Yogendra P; Joshi Lakhey, Paleswan (Journal of Institute of Medicine Nepal, 2021)
Introduction Morbidity after pancreaticoduodenectomy (PD) still remains high. Postoperative pancreatic fistula (POPF) is the most common cause of increased morbidity after PD. Assessment of predictability of risk score for severe postoperative complications was the objective of this study.MethodsThis was a retrospective observational study. Patients undergoing pancreaticoduodenectomy at Tribhuvan University Teaching Hospital (TUTH) between January 2017 to December 2017 were included in the study. Variables were recorded from case sheets of the patients. The “Risk Score” was calculated using the pancreatic duct diameter and body mass index (BMI). Association of risk score and severe postoperative complications were analyzed.ResultsA total number of patients were 43, including 23 (53.5%) males and 20 (46.5%) females. The mean age was 57.09 ± 11.85 years ranges from 29 years to 76 years. The POPF and delayed gastric emptying (DGE) was 23.3% (10/43); and post-pancreaticoduodenectomy hemorrhage (PPH) was 11.6% (5/43). Severe postoperative complications were present in 13.9% (6/43) patients. In univariate analysis, pancreatic duct diameter (p=0.045) and Risk Score (p=0.02) were significantly associated with severe postoperative complications after PD. However none of them were significant in multivariate analysis.ConclusionRisk score failed to predict severe postoperative complication after pancreaticoduodenectomy.